Assessment of Retinal and Choroidal Alterations in Women With Iron-Deficiency Anemia: An Optical Coherence Tomography Study - Uğurlu, Adem; Taşlı, Nurdan Gamze; İçel, Erel (Cerrahpaşa Medical Journal, 2021)
Objective: To evaluate the retinal and choroidal thicknesses in women with iron-deficiency anemia (IDA) by enhanced-depth imaging optical coherence tomography (EDI-OCT) and to compare the results with healthy controls. Methods: Forty reproductive-aged female patients who had IDA and 40 healthy female control were enrolled in the study. Laboratory data including serum hemoglobin (Hb), serum iron, ferritin, and mean corpuscular volume (MCV) were recorded. The average peripapillary retinal nerve fiber layer (pRNFL) thicknesses were measured for all study participants. The central retinal thickness (CRT) and choroidal thickness (CT) in the foveal region and 500 μm in the nasal and temporal directions were analyzed by EDI-OCT. Results: Any significant differences between the control and the patient groups were not determined in comparisons of age, intraocular pressure, central corneal thickness, and axial length (P > .05). The mean CRTs were 238.4 ± 32.1 μm [201-276] and 233.9 ± 29.9 μm [203-268] in control and patient groups, respectively (P = .259). The mean CTs were 295.5 ± 45.9 μm [245-339] in the healthy controls and 271.9 ± 41.3 μm [230-319] in the patients with IDA (P < 0.001). The average pRNFL thickness was significantly lower in the patient group (P < .001, 128.4 ± 12.5 μm vs. 107.8 ± 13.9 μm). A positive correlation was found between serum Hgb, iron, MCV, ferritin values with the pRNFL, and CT (P < .001). No correlation was found between hematological outcomes and mean age, CRT, IOP, CCT, and AL measurements. Conclusion: CT in women with IDA was significantly thinner compared to healthy controls. Choroidal thickness changes may be observed in patients with IDA before significant ocular disorders, especially ischemic changes, occurred. Cite this article as: Uğurlu A, Taşlı N, İçel E. Assessment of retinal and choroidal alterations in women with iron deficiency anemia: An optical coherence tomography study. Cerrahpaşa Med J. 2021;45(3):167-172.